Trust, privacy and security in digital business : 15th International Conference, TrustBus 2018, Regensburg, Germany, September 5-6, 2018, Proceedings /: 15th International Conference, TrustBus 2018, Regensburg, Germany, September 5-6, 2018, Proceedings. (2018) - Unknown
No abstract available